The chimeric repressor for the GATA4 transcription factor improves tolerance to nitrogen deficiency in Arabidopsis - Shin, Ji Min; Chung, KwiMi; Sakamoto, Shingo; Kojima, Soichi; Yeh, Chuan-Ming; Ikeda, Miho; Mitsuda, Nobutaka; Ohme-Takagi, Masaru (Plant Biotechnology, 2017)
Nitrogen limits crop yield, but application of nitrogen fertilizer can cause environmental problems and much fertilizer is lost without being absorbed by plants. Increasing nitrogen use efficiency in plants may help overcome these problems and is, therefore, an important and active subject of agricultural research. Here, we report that the expression of the chimeric repressor for the GATA4 transcription factor (35S:GATA4-SRDX) improved tolerance to nitrogen deficiency in Arabidopsis thaliana. 35S:GATA4-SRDX seedlings were significantly larger than wild type under nitrogen-sufficient and -deficient conditions (10 and 0.5 mM NH4NO3, respectively). 35S:GATA4-SRDX plants exhibited shorter primary roots, fewer lateral roots, and higher root hair density compared with wild type. The expression levels of NITRATE TRANSPORTER 2.1, ASPARAGINE SYNTHETASE and NITRATE REDUCTASE 1 were significantly higher in roots of 35S:GATA4-SRDX plants than in wild type under nitrogen-sufficient conditions. Under nitrogen-deficient conditions, the expression of genes for cytosolic glutamine synthetases was upregulated in shoots of 35S:GATA4-SRDX plants compared with wild type. This upregulation of nitrogen transporter and nitrogen assimilation-related genes might confer tolerance to nitrogen deficiency in 35S:GATA4-SRDX plants.